Pengelolaan Tata Usaha dalam Meningkatkan Pelayanan Administrasi Sekolah di SD Negeri 14 Banyuasin 1 - Margareta, Sherly; Akhmad Saputra, Ade (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
Administrative management involves overseeing the flow of data and information that both enters and exits an organization or educational institution. This process ensures that all aspects of communication and documentation are effectively managed. Activities consists of receiving, recording, classifying, processing, storing, typing, duplicating, sending information and data in writing that is needed by educational institutions / schools. This study aims to determine how the management, implementation and constraints of administrative management in improving school administration at SD Negeri 14 Banyuasin 1This research employs a qualitative methodology with a descriptive approach. The subjects of the study included the principal and the head of administration. Data collection was conducted using a combination of observation, interviews, and documentation. The findings reveal that the administrative management at SD Negeri 14 Banyuasin 1 is effectively conducted through meetings and deliberations aimed at developing a comprehensive school administration plan. These gatherings facilitate better communication and collaboration among the principal, head of administration, and teachers. Overall, the implementation of administrative management has been relatively successful in enhancing school administration services at SD Negeri 14 Banyuasin 1. However, challenges remain, including issues related to the lack of discipline among administrative staff and a general lack of awareness regarding their responsibilities.